2018
DOI: 10.1111/ggi.13234
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic burden and 1‐year mortality among older patients discharged from acute care hospital

Abstract: The ACB score at discharge and, to a lesser extent, an increasing ACB score during hospital stay are associated with an increased risk of 1-year mortality in older patients discharged from hospital. Such an association is stronger among patients with cognitive impairment. Geriatr Gerontol Int 2018; 18: 705-713.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
1
21
2
Order By: Relevance
“…In fact, falls are a frequent cause of hospitalization and institutionalization among old people (Zia et al, 2016). Anticholinergics intake has been associated with the presence of recurrent falls, although there is no definitive evidence in this regard (Lattanzio et al, 2018). It has been suggested that drugs with anticholinergic action may not be independently associated with the risk of falls and fractures (Fraser et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, falls are a frequent cause of hospitalization and institutionalization among old people (Zia et al, 2016). Anticholinergics intake has been associated with the presence of recurrent falls, although there is no definitive evidence in this regard (Lattanzio et al, 2018). It has been suggested that drugs with anticholinergic action may not be independently associated with the risk of falls and fractures (Fraser et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There are no conclusive results about greater mortality in hospitalized elderly patients taking anticholinergics. However, mortality has been associated with anticholinergic use in the presence of hyponatremia (Lowry et al, 2011) or delirium (Mangoni et al, 2013), especially in the presence of cognitive impairment (Lattanzio et al, 2018), even 1 year after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 498,056 older individuals participated across the 18 studies, with a sample size range of 71 to 245,410 (McIsaac et al, 2018) people. Two identical study cohorts were each used twice in separate papers (Lattanzio 2018A (Lattanzio et al, 2018a and B (Lattanzio et al, 2018b);Lowry 2011(Lowry et al, 2011(Lowry et al, 2012); as a result, participants were only counted once. Ages ranged from mean 71 years (SD 12) (Agar et al, 2010) to median 93 years (IQR 91-95) (Kidd et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…If multiple results were provided in the same study, the most appropriate result was chosen to be included in the metaanalyses by two researchers (CS and KG) so as not to duplicate the same study population within one meta-analysis (see results). For Lattanzio 2018 A (Lattanzio et al, 2018a) and Lattanzio 2018B (Lattanzio et al, 2018b, one cohort was used for both studies. Again, to avoid cohort duplication, data assessing ACB on the cohort as a whole (Lattanzio 2018A (Lattanzio et al, 2018a) were chosen as more generalizable than data produced after stratification of individuals by Basic Activities of Daily Living (BADL) scores.…”
Section: Strategy For Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation